Theoretical framework of link stability-based forwarding strategy in vehicular ad hoc networks. (2017) - Hanshi, Sabri M.; Kadhum, Mohammad M.; Wan, Tat-Chee
The nature of vehicular ad hoc networks (VANET) brings challenges that prompt researchers to address relevant problems. One of serious challenges is to design a robust routing protocol that is capable of tackling the frequent link disruptions which are caused by vehicle mobility. Geographic forwarding strategy-based routing protocols are found more suitable in highly dynamic network such VANET. Link expiry time-based (LET) routing is being utilised to minimise link breakages in effectively mobile networks. However, it may cause some issues such as increasing delay and routing loops due to non-optimal selection of next-hop. This paper proposes a relative velocity based geographic forwarding (RVGF) strategy which aims to enhance the link stability with respect to geographic information. Relative velocity model is introduced where speed and direction of vehicles are utilised to improve forwarding decisions in VANET. RVGF can help in minimising the probability of link breakage and ensuring high packet delivery.